Targeting brain microvascular endothelial cells: a therapeutic approach to neuroprotection against stroke - Qi-jin Yu; Hong Tao; Xin Wang; Ming-chang Li (Neural Regeneration Research, 2015)
Brain microvascular endothelial cells form the interface between nervous tissue and circulating blood, and regulate central nervous system homeostasis. Brain microvascular endothelial cells differ from peripheral endothelial cells with regards expression of specific ion transporters and receptors, and contain fewer fenestrations and pinocytotic vesicles. Brain microvascular endothelial cells also synthesize several factors that influence blood vessel function. This review describes the morphological characteristics and functions of brain microvascular endothelial cells, and summarizes current knowledge regarding changes in brain microvascular endothelial cells during stroke progression and therapies. Future studies should focus on identifying mechanisms underlying such changes and developing possible neuroprotective therapeutic interventions.